COVID-19 vaccine associated transverse myelitis-Evusheld as an option when vaccination is not recommended due to severe adverse events - William E. Fitzsimmons (Taylor & Francis Group, 2022)
Individuals who experience severe COVID-19-vaccine-related adverse reactions such as transverse myelitis may be precluded from receiving further vaccination to protect from SARS-CoV-2 infection. Although the mechanism of autoimmune spinal cord inflammation resulting in transverse myelitis is unclear, it may be safe to administer antibody therapy for preventing COVID-19. Recently, Evusheld, tixagevimab with cilgavimab, two spike-protein directed monoclonal antibodies were authorized by the U.S. FDA and U.K. MHRA for administration to individuals when vaccination is not recommended. We report the safe administration of Evusheld to a patient who experienced transverse myelitis 11 months previously as a result of receiving the Moderna mRNA vaccine. This patient has experienced no adverse events to Evusheld. Additional experience and data collection are warranted to determine the safety of this prophylactic therapy.